2013
DOI: 10.1039/c3dt51191j
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl–halide complexation in N,N-dimethylformamide: halide coordination trend manifests hardness of [UO2]2+

Abstract: Complexation of [UO2](2+) with Cl(-), Br(-), and I(-) in N,N-dimethylformamide (DMF) was studied by UV-vis absorption spectroscopy and extended X-ray absorption fine structure (EXAFS) to clearly differentiate halide coordination strengths to [UO2](2+). In the Cl(-) system, it was clarified that the Cl(-) coordination to [UO2](2+) in DMF proceeds almost quantitatively. The coordination number of Cl(-) almost quantitatively increases up to 4, i.e., the limiting complex is [UO2Cl4](2-). Logarithmic gross stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…14,15 Indeed, thermodynamic stability of a UO 2 2+ -halido complex in DMF follows the order of hardness of halide ligands, Cl − > Br − > I − . 16 In contrast, such a trend in complexation between UO 2 2+ and heteroatoms like N, O and S, seems not to be well understood systematically, although it would provide essential information to understand the fundamental nature of UO 2 2+ in more depth and to design molecular structures of ligands exclusively interacting with UO 2 2+ . Indeed, several extracting reagents have been successfully developed for separation of Am( iii ) and Cm( iii ) from Ln( iii ) on the basis of difference in coordinating affinities of these metal ions with soft-donor atoms incorporated in the designed ligands.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Indeed, thermodynamic stability of a UO 2 2+ -halido complex in DMF follows the order of hardness of halide ligands, Cl − > Br − > I − . 16 In contrast, such a trend in complexation between UO 2 2+ and heteroatoms like N, O and S, seems not to be well understood systematically, although it would provide essential information to understand the fundamental nature of UO 2 2+ in more depth and to design molecular structures of ligands exclusively interacting with UO 2 2+ . Indeed, several extracting reagents have been successfully developed for separation of Am( iii ) and Cm( iii ) from Ln( iii ) on the basis of difference in coordinating affinities of these metal ions with soft-donor atoms incorporated in the designed ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Although no isosbestic points were observed in Fig. 4, principal component analysis (PCA) 42,43 has suggested that a total of 2 components are involved in this spectral series. This result corroborates the occurrence of eqn (3) in the current system.…”
Section: (Esi †) V Ini Is Proportional To [Opph 3 ] Freementioning
confidence: 89%
“…Indeed, the equatorial coordination environment in the case of uranyl complexes which contains a robust axial structure may offer some selectivity for the chemical reaction. For the nucleophilic acyl substitution of acetic anhydride, Takao et al [110] have experimented with four different uranyl complexes 17-20 [111][112][113][114] as catalyst (Figure 9). For this, substrates such as acetic anhydride and ethanol were chosen for a model reaction system.…”
Section: Nucleophilic Acyl Substitutionmentioning
confidence: 99%